(untitled) (Global Journal of Science Frontier Research, 2021)
Integrated duck cum fish farming is suitable for developing countries like Nepal as it uses the locally available resources. This study was conducted for 120 days in an earthen pond of area 575 m 2 . The fish stocked were Labeorohita(25%), Cirrhinus Mrigala (10%), Cyrinuscarpio (25%), Aristichthys nobilis (5%), Ctenopharyngodonidella (15%) and Oreochromis niloticus(20%) with the stocking density of 13000 fingerlings/ha. Fish were fed with dough formed with locally available ingredients like MOC and rice bran containing 20% CP at the rate of 2% of total body weight daily. The results showed the extrapolated GFY to be 4.0 t/ha/yr and extrapolated NFY was 2.9 t/ha/yr of total fish species. The total fish yield was 53.2 kg and the total feed supplied was 76.8 kg. The overall survival rate of fish was 66.0% whereas the AFCR was 1.4. Duck growth showed a normal trend from mean stock weight of 161±69.8 g/duck to mean harvest weight 1114.4±296.4 g/duck. Similarly, daily weight gain was 7.95 g/duck/day. The benefit: cost ratio for duck and fish production was 1.24and 1.65 respectively. This study concludes that carp-tilapia polyculture in integration with duck is reliable, economically viable, and effective for the small-scale fish farmers as well as the marginal groups.